2019
DOI: 10.12659/msmbr.915067
|View full text |Cite
|
Sign up to set email alerts
|

Spalt-Like Transcription Factor 1 (SALL1) Gene Expression Inhibits Cell Proliferation and Cell Migration of Human Glioma Cells Through the Wnt/β-Catenin Signaling Pathway

Abstract: Background The spalt-like transcription factor 1 (SALL1) gene is a member of the Krüppel-associated box-containing zinc finger proteins (KRAB-ZFPs) and has been shown to modulate the onset and progression of human tumors. This study aimed to investigate the regulatory effects and mechanisms of SALL1 gene expression in human glioblastoma and glioma cells and tissue samples from patients with cerebral glioma. Material/Methods The human glioblastoma cell lines, LN229, U87-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Since the function of miRNAs are realized via modulating their target genes’ mRNA expression [ 26 ], we here conducted the bioinformatics analysis and verification experiment, and revealed that spalt like transcription factor 1 (SALL1) was one of the potential downstream target genes of miR-1243. The SALL1 is a member of Krüppel-associated box-containing zinc finger proteins (KRAB-ZFPs), and has been revealed to modulate the initiation and progression of human tumors [ 27 , 28 ]. SALL1 acted as a tumor suppressor gene in human glioma [ 27 ] and breast cancer ( Ma et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the function of miRNAs are realized via modulating their target genes’ mRNA expression [ 26 ], we here conducted the bioinformatics analysis and verification experiment, and revealed that spalt like transcription factor 1 (SALL1) was one of the potential downstream target genes of miR-1243. The SALL1 is a member of Krüppel-associated box-containing zinc finger proteins (KRAB-ZFPs), and has been revealed to modulate the initiation and progression of human tumors [ 27 , 28 ]. SALL1 acted as a tumor suppressor gene in human glioma [ 27 ] and breast cancer ( Ma et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The SALL1 is a member of Krüppel-associated box-containing zinc finger proteins (KRAB-ZFPs), and has been revealed to modulate the initiation and progression of human tumors [ 27 , 28 ]. SALL1 acted as a tumor suppressor gene in human glioma [ 27 ] and breast cancer ( Ma et al, 2018 ). Further, miR-4286 may exert its tumor-promoting actions, in part, by downmodulating SALL1 in prostate cancer (PCa) [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…One SNP near SALL1 , in relation to CRP, both overall and in the obesity strata, is associated with breast cancer risk. SALL1 is a member of the SALL gene family, encoding a multiple zinc-finger transcription repressor that regulates organogenesis and development of embryonic stem cells 69 – 71 . The role of the SALL genes (particularly SALL2 and SALL4 ) in tumorigenesis has recently been investigated as a tumor suppressor for ovarian and Wilms’ tumors 72 , 73 , hepatoblastoma, and gastric carcinoma 74 , 75 .…”
Section: Discussionmentioning
confidence: 99%
“…In cancer, Sall1 has been found to be downregulated in breast cancer, glioblastoma ( 77 ), and myeloid leukemia, supporting its role as a tumor suppressor ( 76 ). In support of such a tumor suppressor role, Sall1 has been found to be a target of oncogenic miRNAs.…”
Section: Spalt-like Transcription Factormentioning
confidence: 97%
“…Furthermore, overexpression of Sall1 negatively impacts cell cycle progression and proliferation through the suppression of β -catenin, antagonizing the Wnt/ β -catenin signaling pathway accordingly by targeting Wnt downstream targets Cyclin D1 (Ccnd1) and c-Myc oncogene. In addition, Sall1 is affecting the progression of cancer through the upregulation of the epithelial marker E-cadherin and downregulation of the mesenchymal markers vimentin and N-cadherin, driving mesenchymal-to-epithelial transition ( 77 ).…”
Section: Spalt-like Transcription Factormentioning
confidence: 99%